2018
DOI: 10.1177/1040638718812927
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a spectrophotometric method for GGT measurement in canine urine and determination of the urine GGT-to-creatinine ratio reference interval and biological variation in 41 healthy dogs

Abstract: The urine gamma-glutamyl transferase (GGT)-to-creatinine ratio has been used to monitor patients at risk of acute renal injury. We validated the spectrophotometric quantification of GGT in urine in a commercial biochemistry analyzer.The assay was precise, accurate, and linear. Intra-assay precision was 3.59% in 4 samples, with GGT concentrations of 47-195 U/L. Inter-assay precision in 3 samples with activities of 11-51 U/L was 7.74%. Accuracy was 97.3%, with an absolute bias of 2.7 U/L. Urine GGT was unaffecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Evidence suggests that uALb/uCr and uNGAL/uCr values are unlikely to be signi cantly affected by microscopic haematuria and haemoglobinuria, respectively (52). Likewise, haematuria and haemoglobinuria are unlikely to signi cantly affect uGGT/uCr (37,38), but it is unknown to what extent results for the other biomarkers in this study might be affected. Although the extent to which myoglobinuria might interfere with biomarker measurement is unknown, it is thought unlikely to in uence the overall conclusions of this study since this was observed only in one dog.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Evidence suggests that uALb/uCr and uNGAL/uCr values are unlikely to be signi cantly affected by microscopic haematuria and haemoglobinuria, respectively (52). Likewise, haematuria and haemoglobinuria are unlikely to signi cantly affect uGGT/uCr (37,38), but it is unknown to what extent results for the other biomarkers in this study might be affected. Although the extent to which myoglobinuria might interfere with biomarker measurement is unknown, it is thought unlikely to in uence the overall conclusions of this study since this was observed only in one dog.…”
Section: Discussionmentioning
confidence: 75%
“…There are several possible explanations for a lack of increase in uALP in our study compared to others. Poor assay sensitivity might be considered most likely, but differences in timing and storage of samples are also possible explanations (38). An optimal uALP detection window of less than 12 hours after renal insult is reported in humans (39); thus, the detection window may have been missed in our study.…”
Section: Discussionmentioning
confidence: 78%
“…GGT is a transferase enzyme present in the cell membranes of various tissues [29]. In kidneys, GGT releases in the renal tubular lumen after injury of the microvilli of the luminal surface of renal tubular epithelial cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible explanations for a lack of increase in uALP in our study compared to others. Poor assay sensitivity might be considered most likely, but differences in timing and storage of samples are also possible explanations [ 38 ]. An optimal uALP detection window of less than 12 h after renal insult is reported in humans [ 39 ]; thus, the detection window may have been missed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that uALb/uCr and uNGAL/uCr values are unlikely to be significantly affected by microscopic haematuria and haemoglobinuria, respectively [ 52 ]. Likewise, haematuria and haemoglobinuria are unlikely to significantly affect uGGT/uCr [ 37 , 38 ], but it is unknown to what extent results for the other biomarkers in this study might be affected. Although the extent to which myoglobinuria might interfere with biomarker measurement is unknown, it is thought unlikely to influence the overall conclusions of this study since this was observed only in one dog.…”
Section: Discussionmentioning
confidence: 99%